A metabolite of nobiletin, 4′-demethylnobiletin and atorvastatin synergistically inhibits human colon cancer cell growth by inducing G0/G1 cell cycle arrest and apoptosis. Issue 1 (24th October 2017) - Wu, Xian; Song, Mingyue; Qiu, Peiju; Li, Fang; Wang, Minqi; Zheng, Jinkai; Wang, Qi; Xu, Fei; Xiao, Hang
Abstract : Combining different chemopreventive agents is a promising strategy to reduce cancer incidence and mortality due to potential synergistic interactions between these agents. Abstract : Combining different chemopreventive agents is a promising strategy to reduce cancer incidence and mortality due to potential synergistic interactions between these agents. Previously, we demonstrated that oral administration of nobiletin (NBT, a citrus flavonoid) at 0.05% (w/w, in diet) together with atorvastatin (ATST, a lipid-lowering drug) at 0.02% (w/w, in diet) produced much stronger inhibition against colon carcinogenesis in rats in comparison with that produced by NBT (at 0.1% w/w in diet) or ATST (at 0.04% w/w in diet) alone at higher doses. To further elucidate the mechanism of this promising synergy between NBT and ATST, herein, we measured the levels of NBT, its major metabolites and ATST in the colonic tissue of rats fed NBT (0.05% w/w, in diet) + ATST (0.02% w/w, in diet), and determined the mode of interaction between the major NBT metabolite and ATST in inhibiting colon cancer cell growth. HPLC-MS analysis showed that 4′-demethylnobiletin (4DN) is the most abundant metabolite of NBT with a level about 5-fold as high as that of NBT in the colonic tissue, which indicated the potential significance of 4DN in mediating the biological effects of NBT in the colon. We found that co-treatments of 4DN/ATST at 2 : 1 concentration ratio produced much stronger growth inhibitory effects on human colon cancer HT-29 cells than 4DN or ATST alone, and isobologram analysis confirmed that this enhanced inhibitory effect by the 4DN/ATST combination was highly synergistic. The co-treatment of 4DN/ATST led to G0/G1 cell cycle arrest and induced extensive apoptosis in HT-29 cells. Furthermore, the 4DN/ATST co-treatment profoundly modulated key signaling proteins related to the regulation of the cell cycle and apoptosis. Our results demonstrated a strong synergy produced by the 4DN/ATST co-treatment in inhibiting colon cancer cell growth, which provided a novel mechanism by which NBT/ATST in combination synergistically inhibit colon carcinogenesis.